The Role of Online Relationship Marketing Programs toward Influencing University Students to Purchase Different Clothing Products (Cross-Buying) Under the Same Online Retailer in Malaysia - Mshigati, Elisafi Willson (2013)
Since the introduction of internet and Worldwide Web, business environment has rapidly changed from shopping in physical stores to online shopping. In recent years the clothing industry has taken a new turn where more people prefers online shopping over purchasing in physical retail stores. This new trend has intensified the level of competition in the clothing industry with more online retailers coming into the industry from all over the world like America, Europe and China. The biggest challenge among marketers in clothing industry hasn’t been only how to recruit new customers and keep their existing customers but also to persuade them to buy different products under the same retailer which is referred as cross-buying. This research will focus on finding how online relationship marketing programs like online rebates, discounts, accumulation of points, sending online cards and the design of the online platform may influence customers to purchase different clothing products under same retailer. The sample size of 200 University students from INTI International University will be collected to do analysis. The findings of this research will help to increase knowledge to academicians and scholars on the field of cross-buying from online perspective, help marketers to understand how to cultivate profitable long-term customer relationship through cross-buying and the government in its role improving the availability of internet access to boost the business sector which contributes to national GDP.